Pseudomonas aeruginosa septicemia - Bocanegra C., Manuel (1967)
Experiments in burned mice were conditioned so that, with adequate numbers of living germs Pseudonoma aeruginosa or their toxins, as high as 80 mortalities occur to 100%, after 72 hours of the burn produced and inoculum. These animals and were treated with standard gamma globulin horse (6%), immunized against Pseudonoma aeruginosa, "antiserum" and dilute the hundredth human gamma globulin to 16%, dilute the hundredth equally. The degree of protectiveness conferred by these two types of gamma globulin against inocula were evaluated by the decrease in mortality that occurred in each case.